Effects of Sewage Sludge used as Fertilizer on Heavy Metal Contents of Bird's-Foot Trefoil (Lotus corniculatus L.) and Soil - Saruhan, V.; Gul, I.; Kusvuran, A.; Aydin, F. (Asian Journal of Chemistry, 2011)
This study was carried out to determine the effects of the sludge which was provided from a wastewater refinement facility of Municipality of Diyarbakir on bird's-foot trefoil plant production and its soil properties. For this purpose, the increasing level of sewage sludge has been applied to the soil samples which are taken from the plant rotation field of Dicle University campus area in Turkey and this sludge was left. At the end of study, the chemical properties of the soil have been determined and the results have been compared statistically. In this study three times reiterated randomized blocks design type has been established in the pod to determine the effects of the sludge to the plants and also the mineral content (Hg, Cr, Zn and Ni) of bird's-foot trefoil plant. The sludge that was applied to the soil with increasing amounts, raised the heavy metal content of bird's-foot trefoil plant, but this raising did not line-out for allowable limit.